Climate change and sustainability in ASEAN countries - DING, David K. (Institutional Knowledge at Singapore Management University, 2022)
The ASEAN region is one of the most susceptible regions to climate change, with three of its countries—Myanmar, the Philippines, and Thailand—among those that have suffered the greatest fatalities and economic losses because of climate-related disasters. This paper reveals that the ASEAN’s environmental performance is sorely lagging other regions despite evidence of its cohesive and comprehensive efforts to mitigate emissions and build up adaptive capacity to climate-related disasters. Within the ASEAN, there exist gaps in environmental performance between each country. This suggests that increased cooperation between individual ASEAN countries is pertinent for the region to collectively combat climate change. In addition, we show that government effectiveness has a positive influence on a country’s climate performance, signifying that a government’s strong commitment to governance is necessary in the fight against climate change.